Symmetry breaking in spreading RAT2 fibroblasts requires the MAPK/ERK pathway scaffold RACK1 that integrates FAK, p190A-RhoGAP and ERK2 signaling - Klímová, Zuzana; Bráborec, Vojtěch; Maninová, Miloslava; Čáslavský, Josef; Weber, Michael J; Vomastek, Tomáš (Biochimica et biophysica acta, 2016)
The spreading of adhering cells is a morphogenetic process during which cells break spherical or radial symmetry and adopt migratory polarity with spatially segregated protruding cell front and non-protruding cell rear. The organization and regulation of these symmetry-breaking events, which are both complex and stochastic, are not fully understood. Here we show that in radially spreading cells, symmetry breaking commences with the development of discrete non-protruding regions characterized by large but sparse focal adhesions and long peripheral actin bundles. Establishment of this non-protruding static region specifies the distally oriented protruding cell front and thus determines the polarity axis and the direction of cell migration. The development of non-protruding regions requires ERK2 and the ERK pathway scaffold protein RACK1. RACK1 promotes adhesion-mediated activation of ERK2 that in turn inhibits p190A-RhoGAP signaling by reducing the peripheral localization of p190A-RhoGAP. We propose that sustained ERK signaling at the prospective cell rear induces p190A-RhoGAP depletion from the cell periphery resulting in peripheral actin bundles and cell rear formation. Since cell adhesion activates both ERK and p190A-RhoGAP signaling this constitutes a spatially confined incoherent feed-forward signaling circuit.
Keywords: fokální adhezní tyrosinkinasy; Repressor Proteins; Gene Knockdown Techniques; Animals; pohyb buněk; Focal Adhesion Protein-Tyrosine Kinases; Mitogen-Activated Protein Kinase 1; Actins; aktiny; Cell Shape; MAP Kinase Signaling System; GTP-Binding Proteins; Rats; MAP kinasový signální systém; tvar buňky; Cell Adhesion; fibroblasty; Phenotype; mitogenem aktivovaná proteinkinasa 1; buněčná adheze; proteiny vázající GTP; fenotyp; zvířata; represorové proteiny; Fibroblasts; Models, Biological; genový knockdown; biologické modely; umlčování genů; krysa rodu Rattus; Cell Movement; Gene Silencing